(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Indian energy sector is unique both in terms of its organization as well as complexity whichresults from the fact that India is a rapidly growing economy with huge disparity in income and lifestyles.About 68 percent of Indian population still lives in rural areas and depends upon non commercial sourcesof energy such as fuel wood, biomass and agricultural rest for their requirements of energy, like lightingand cooking. The present study has been conducted to discuss the policy framework and current statusof Indian energy sector. In the results of the study, the concept of Indian energy sector has beendiscussed in detail. Further, various challenge in the way of Indian energy sector have also beendiscussed.